CONSEQUENCES OF THE COVID-19 PANDEMIC IN THE EUROPEAN UNION FROM THE PERSPECTIVE OF GENERAL GOVERNMENT FINANCES – AN ANALYSIS BASED ON THE SOCIAL ACCOUNTING MATRI - Joanna Trębska (Polityki Europejskie, Finanse i Marketing, 2023)
The aim of the paper is to assess the effects of the COVID-19 pandemic from the perspective of income circulation processes in the economies of the European Union. The empirical study is based on statistical data compiled according to ESA2010 standards, published by the European Commission in the Eurostat database. The fundamental quantitative relationships between entities grouped into institutional sectors have been synthetically presented in the form of a social accounting matrix (SAM). The analyses of simple macroeconomic indicators show the growing importance of the government sector due to the pandemic. This is evidenced by the growing involvement of this sector in consumption, accumulation and income redistribution between institutional sectors.Simulation analyses based on the SAM model determine to what extent the contribution of the government sector to GDP results directly through feedback loops from final demand and to what extent from current and capital transfers.